Engineering Education and Labor Efficiency Skills: Experience of Portugal - M. T. Restivo; Ju. N. Ziyatdinova (Высшее образование в России)
In the future, the work of individual engineers, performance skills and, consequently, their efficiency are likely to be conceptualized and driven based on different methodologies, approaches and initiatives. Such capabilities may be conveyed by a number of disciplines and other academic opportunities along the engineering degree programs. Taking into account the goals of the “Integrative Training of Line Engineers at Oil, Gas and Chemical Enterprises for Increasing Labor Efficiency” Synergy-2018, the authors attempted to convey the personal perception of how to contribute, at various organizational/institutional levels, to the labor efficiency skills of engineering students. The aim of the analysis is twofold: i) exploring Institutional agendas aligned with this context and ii) consider the result of the personal efforts in a lab oriented both to engineering education and to R&D activities.